Vida, Pensamiento y Obras de Simón Bolívar en la Gran Colombia - Bajaña Ortiz, Edinson Jasmil (2018)
Simón Bolívar, masterful character, who undoubtedly left a great contribution to our education, was enough reason to pose it as a theme for the design of the mural, Life, Thoughts and Works of Simón Bolívar, we consider all the relevant aspects of this character, since that are based on the pedagogy of our university, making a perfect contract. Our mural in mosaic composed of several triangular pieces of varied sizes, that allow to give a better finish to the work, with its tones help to enhance the place where it is located, its bright and striking colors invite the viewer to observe and be participants in this reunion between art and imagination. For the elaboration of this mural we have carried out its respective investigation, about the life, thought and works of the liberator, since due to all this process we will be able to understand the ideals of Bolivar, especially in education. As well as the technique of mosaic mural painting and its elaboration. The purpose of sovereignty initiated by the Council of Ministers in the removal of Bolivar, subsequently admonished by him, the desire for autonomy and independence of the populations and the state skill that asked for a discernment to be formulated with unconditional independence, by publications or by other means, without trying to affect the nature of the government. For the great Colombia in 1825 was an event that implanted a sudden omen. Leonardo Infante, a Venezuelan officer, was tried and sentenced to death because of the violent death of Lt. Francisco Perdomo, a fact that arose in Bogotá. The Venezuelan governor obtained flying buttresses in his country of origin and the dissatisfied ones congregated around him; the criticisms against the administration were created increasingly excessive and increased in great magnitude and all the fragmented engaged in a union conversation. The discriminatory ideology was emphasized giving way to a conflict in 1826 that broke out between the civil and military representations, which was consistent with the suspension of the Gran Colombia. Simón Bolívar El Libertador, had his doubts about the instability of the alliance that he enjoyed and had dreamed for these countries. In 1826 the civic-military summary was accredited as La Cosiata, for an argument consistent with the recruitment of the residents in the armies, which declined in a succession of accusations, which were evasive for the perfection of a naive separatist effect. Paez as of 1830 had several opponents of the Parliament, component of Venezuela that compensated to congregate in the city of Valencia, that required the exclusion of El Libertador Simón Bolívar, the appointment of Páez as the leader of the districts and the recognition of the obligations with lands and refugee individuals. Paez has beaten a supposedly equitable management, and moved to Caracas and on December 24, 1830, with the evasion of requesting a tribute for the sustenance of the regiment, convenes another congress, where he tries to administer an exhibition to the Liberator that supports the points themselves of view competent in the congress. On December 28, they leave the jurisdiction of Bolívar, to issue that Venezuela is separated from Gran Colombia, and they entrust Páez with superiority, providing him with a delegation to summon a parliament that represents a constitution, to demand the Privileged director not to admit the entry of Bolivar to Venezuela; To warn this uprising against General Páez, affirming that everyone, in order to maintain their independence, is left to loose the holocaust of their lives and capital if it were inevitable. Bolivar had exhibited before the Legislative Parliament his inevitable resignation to the leadership of the Government and the first of March 1830, entrusted to General Domingo Caicedo, a widespread succession of the Constitution, the Parliament of Bogota appointed as President and Vice President of the Republic, re-offending these obligations in Don Joaquin Mosquera and General Domingo Caicedo, on September 22 the Parliament of Valencia condemned the new Constitution ,wihich was sitting conclusively the dispersion of the Great Colombia